SYARIAH ECONOMIC DEVELOPMENT COMMUNICATION SYSTEM AND ITS IMPLEMENTATION IN THE BANKING FIELD - Mas Khairani (Proceeding International Seminar of Islamic Studies, 2023)
Islamic economics is known as an alternative solution for mankind to carry out economic activities. This system originates from Islamic teachings, which principally require the involvement of God in every activity. Even though it has been an alternative choice for a long time, it seems that this system has not been fully communicated to Indonesian society. This is evidenced by the relatively small market share of Islamic banking, even though the majority of Indonesia's population is Muslim. This article aims to analyze the communication system applied in the Islamic economic system, especially in the banking sector. The method used in this research is the library research method. The results of the study show that the course of the Islamic economic system in the banking sector, which has been implemented for more than 30 years in this country, has not developed significantly due to a weak communication system that has not touched market logic.